Gambaran Jumlah dan Jenis Leukosit pada pasien Rumah Sakit Umum Daerah Abdul Wahab Sjahranie Samarinda - Aminuddin, Muhammad Fahmi; Soda, Amelia; Mawardani, Maya Tamara (Institut Teknologi Kesehatan dan Sains Wiyata Husada Samarinda, 2025)
Leukocyte examination is divided into two types, namely the examination of the number and type of leukocytes in the blood. The leucocyte count measures the absolute number of leucocytes in a unit volume of blood. Meanwhile, the leucocyte type count records the proportion (%) of each leucocyte type such as neutrophils, eosinophils, basophils, monocytes and lymphocytes from the total leucocytes. Information from this examination is very useful for detecting and describing the development of disease in the body, especially in cases of infection. This study aims to determine the results of leukocyte examination, internal quality assurance, Good Laboratory Practice (GLP) Implementation and Occupational Health and Safety (K3) Implementation at Abdul Wahab Sjahranie Samarinda Regional General Hospital (RSUD AWS Samarinda). This research was conducted from 15 January to 23 February 2024. The results of this study obtained 970 samples, most of which were in the normal range, although there were also low (113 samples) and high (134 samples). Absolute neutrophil results with normal levels of 79.1%, high 17.8%, and low (3.1%). The absolute lymphocyte result was 79.1% normal, 3.9% high, and 17.0% low. Absolute monocyte results with normal levels: 93.3%, high: 5.2%, and low 1.5% and absolute eosinophil results with normal levels: 95.1% and high: 4,9%. Absolute basophil results were 99.1% normal and 0.9% high. The conclusion of this observation was that 134 patients (13.8%) had leucocytosis and 112 patients (11.5%) had leucopenia. In the observation of strengthening the internal quality of leucocyte examination with the Mindray CAL 8000 tool has been carried out according to procedures. GLP and K3 have been carried out in accordance with the Standard Operational Procedure (SOP) in the Hematology Laboratory of AWS Samarinda Hospital.